KAJIAN BANGUNAN LAWANG SEWU, SEMARANG, JAWA TENGAH SEBAGAI RUANG INTERAKSI SOSIAL - Darmayanti, Tessa Eka; Santoso, Miky Endro (Program Studi Desain Interior Unikom, 2023)
This article was born from the author's experience regarding the existence of social space in Lawang Sewu, Semarang which is the focus of the research. During the Dutch colonial era, Lawang Sewu was a Dutch railway office building known as NISM (Nederlandsch-Indische Spoorweg Maatschappij). Lawang Sewu has become a tourist destination with a change in function from an office to a museum. These changes have an impact on various activities in the Lawang Sewu complex which give birth to various social spaces, and space cannot be separated from human life. Space is often only identified through visible forms, but space is also intangible, which comes from ideas, experiences, memories, culture, and history. The aim of this research is to provide a new perspective in looking at the